Enhancing and Measuring Consumers’ Motivation, Opportunity, and Ability to Process Brand Information from Ads - Maclnnis, Deborah J.; Moorman, Christine; Jaworski, Bernard J. (Journal of Marketing, 1991)
Considerable research suggests that advertising executional cues can influence communication effectiveness. Related research indicates that communication effectiveness is in part driven by consumers’ motivation, opportunity, and ability (MOA) to process brand information from an ad. However, little research has explicitly linked executional cues to communication effectiveness via their impact on MOA and levels of processing. The authors present a framework that explicitly provides such a linkage. The framework highlights the mediational role of MOA in the relationships among executional cues and communication outcomes. It also provides a theoretical account that links apparently disparate cues to their common effects on motivation, opportunity, or ability. The framework is complemented by a critical review of current measures of MOA and proposed measures based on the review. Research issues raised by the framework and the proposed measures are discussed.